Altered Cytokine Expression and Barrier Properties after In Vitro Infection of Porcine Epithelial Cells with Enterotoxigenic Escherichia coli and Probiotic Enterococcus faecium. (21st May 2017) - Kern, Martina; Günzel, Dorothee; Aschenbach, Jörg R.; Tedin, Karsten; Bondzio, Angelika; Lodemann, Ulrike
Abstract : The aim of the present study was to elucidate the effects of the probiotic feed additive Enterococcus faecium NCIMB 10415 ( E. faecium ) on porcine jejunal epithelial cells (IPEC-J2) during an in vitro challenge with enterotoxigenic Escherichia coli (ETEC). Cells were incubated with E. faecium, ETEC, or both, and the effects on barrier function and structure and intra- and intercellular signaling were determined. Coincubation with E. faecium abolished the ETEC-induced decrease in transepithelial resistance ( R t ) (p ≤ 0.05 ). No differences were seen in the expression levels of the intercellular connecting tight junction proteins examined. However, for the first time, a reorganization of the monolayer was observed in ETEC-infected cells but not in coincubated cells. ETEC induced an increase in cytotoxicity that was prevented by coincubation (p ≤ 0.05 ), whereas apoptosis rates were not affected by bacterial treatment. ETEC increased the mRNA expression and release of proinflammatory cytokines TNF- α, IL-1 α, and IL-6 which could be prevented by coincubation for TNF- α mRNA expression and IL-6 protein (p ≤ 0.05 ). Likewise, cAMP concentrations elevated by ETEC were reduced in coincubated cells (p ≤ 0.05 ). These findings indicate a protective effect of the probiotic E. faecium on inflammatory responses during infection with ETEC.